The Direction Of Islamic Banking Development In Pakistan From Financial Experts Opinion - Ghutai, Gul (2021)
The development in the industry of Islamic Banking reflects the supportive yet enabling environment provided by Government to promote growth in the market share of assets while providing sufficient infrastructure for facilitating new entrants. Also, by targeting improvement measures through regulators in existing Islamic banking entities to achieve socio-economic wellbeing of the masses. Since 2002, the industry of Islamic Banking in Pakistan is operating parallel to conventional banking setup. The existence of conventional banking setup losses its legitimacy to be operative in Pakistan as it goes against the Islamic ideology of the Country. However, efforts towards Islamization of financial setup started since long ago due to religious and constitutional obligations but to date interest free banking has not been developed as the only full fledge mode of banking in Pakistan. Thus, Three specific objectives of the study are, to determine the status of development of Islamic banking in Pakistan, to analyse the development of Islamic banking in Pakistan with respect to financial experts’ opinion and to conclude the development of Islamic banking in Pakistan. The qualitative research methodology is pursued throughout the study and conceptual framework is built by adopting inductive paradigm while semi structured in dept interview instrument has been used to represent financial experts’ opinions as interview informants to assess the direction of Islamic banking development in Pakista